2005
DOI: 10.1172/jci24196
|View full text |Cite
|
Sign up to set email alerts
|

Increased glucose tolerance and reduced adiposity in the absence of fasting hypoglycemia in mice with liver-specific Gsα deficiency

Abstract: The G protein G s α is essential for hormone-stimulated cAMP generation and is an important metabolic regulator. We investigated the role of liver G s -signaling pathways by developing mice with liver-specific G s α deficiency (LGsKO mice). LGsKO mice had increased liver weight and glycogen content and reduced adiposity, whereas survival, body weight, food intake, and metabolic rates at ambient temperature were unaffected. LGsKO mice had increased glucose tolerance with both increased glucose-stimulated insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 46 publications
3
118
0
Order By: Relevance
“…Gsa has been shown to be involved in the regulation of the production of cAMP; 18,19 it has also been proposed that XLas is an antagonist of Gsa. For example, this may mean that Gsa is responsible for the production of cAMP and XLas for suppression of cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Gsa has been shown to be involved in the regulation of the production of cAMP; 18,19 it has also been proposed that XLas is an antagonist of Gsa. For example, this may mean that Gsa is responsible for the production of cAMP and XLas for suppression of cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the effect of RIαB, liver-specific knockout of Gsα in mice leads to improved glucose tolerance and increased insulin sensitivity in liver and skeletal muscle. These mice also had increased glycogen content and decreased expression of gluconeogenic genes in the liver, accompanied by hypoglycemia and more than 100-fold higher blood glucagon levels compared with controls (Chen et al 2005b), indicating a condition of glucagon resistance. Recently, it was shown that mice with deficiency of the RIIα subunit of PKA had decreased PKA activity in the liver and showed resistance to diet-induced insulin resistance and diabetes (London et al 2014).…”
Section: R99mentioning
confidence: 92%
“…Immunoblots of tissue extracts, using a G s ␣-specific antibody, were performed as described in ref. 34. Mice were genotyped by PCR as described in ref.…”
Section: Methodsmentioning
confidence: 99%